Reproductive biology of the silky shark Carcharhinus falciformis (Müller & Henle, 1839) in waters off Côte d’Ivoire (West Africa) - Koua Clément n’Gouan; Kouadio Justin Konan; Kouassi Yves Narcisse Kouamé; Oi Edia Edia (Journal of Fisheries, 2023)
Since 2008, the quantity and size of silky shark, Carcharhinus falciformis decrease drastically in catches of artisanal driftnet fishery operating in the coastal waters off Côte d’Ivoire. The objective of this study was to describe the reproductive biology of this species, based on 336 specimens (162 males and 174 females). The total length (TL) of males and female ranged from 81–242 and 79–254 cm respectively. The sex ratio was 0.89:1 (M:F) and 0.93:1 (M:F) in embryos and adults respectively. Males of >180 cm had calciﬁed clasper (17–35 cm) whereas females of >190 cm had oviduct gland length of 18–47 mm. The estimated length at first maturity was 182.8 cm for males and 195.2 cm for females. The range in litter size of three gravid females was 7–9, with an average of 8 embryos of 52–54.5 cm TL were collected in August and December. However, the absence of neonates and scars on females' body, as well as ovulating and differentiating females in catches does not allow a clear determination of its reproductive period in Ivorian waters and therefore, additional research including histological analysis is necessary to better understand the process of spawning of silky shark.